Análisis experimental del transporte de sedimentos en un canal hidrodinámico - Jimenez Sanchez, Melanie Ashley (Machala : Universidad Técnica de Machala, 2025)
This thesis presents an experimental study on sediment transport in a laboratory flume, aiming to analyze the evolution of bedforms and determine the initiation of particle movement. Two experiments were conducted: one focused on identifying bedform transitions under increasing flow rates, and another on calculating the shear stress and comparing it with the critical value defined by Shields’ theory. Hydraulic parameters such as mean velocity, shear stress, friction velocity, Reynolds number, and Shields parameter were determined and analyzed. The results were interpreted based on hydraulic theory and national design standards. The findings reveal the transition between ripples, dunes, and antidunes, and confirm the usefulness of the Shields diagram for the design and operation of irrigation canals, stormwater drains, and desilting basins.
La presente tesis desarrolla un estudio experimental sobre el transporte de sedimentos en un canal de laboratorio, con el objetivo de analizar la evolución de las formas de lecho y determinar el inicio del movimiento de partículas. Se realizaron dos experimentos: uno centrado en la identificación de las formas de lecho bajo caudales crecientes, y otro en el cálculo del esfuerzo cortante comparado con el valor crítico de la teoría de Shields. Se determinaron y analizaron parámetros hidráulicos como la velocidad media, el esfuerzo cortante, la velocidad de fricción, el número de Reynolds y el parámetro de Shields. Los resultados fueron interpretados con base en teoría hidráulica y normas nacionales de diseño. Los hallazgos evidencian la transición entre ripples, dunas y anti-dunas, y confirman la utilidad del diagrama de Shields para el diseño y operación de canales de riego, drenajes pluviales y desarenadores.
Keywords: TRANSPORTE DE SEDIMENTOS; PARÁMETRO DE SHIELDS; FORMAS DE LECHO; ESFUERZO CORTANTE